Cost-effectiveness of a melanoma screening programme using whole disease modelling. (September 2020) - Buja, Alessandra; Rivera, Michele; Girardi, Giovanni; Vecchiato, Antonella; Rebba, Vincenzo; Pizzo, Elena; Sileni, Vanna Chiarion; Palozzo, Angelo Claudio; Montesco, Maria; Zorzi, Manuel; Sartor, Gino; Scioni, Manuela; et al.
Objective: To assess the potential impact of a melanoma screening programme, compared with usual care, on direct costs and life expectancy in the era of targeted drugs and cancer immunotherapy. Methods: Using a Whole Disease Model approach, a Markov simulation model with a time horizon of 25 years was devised to analyse the cost-effectiveness of a one-time, general practitioner-based melanoma screening strategy in the population aged over 20, compared with no screening. The study considered the most up-to-date drug therapy and was conducted from the perspective of the Veneto regional healthcare system within the Italian National Health Service. Only direct costs were considered. Sensitivity analyses, both one-way and probabilistic, were performed to identify the parameters with the greatest impact on cost-effectiveness, and to assess the robustness of our model. Results: Over a 25-year time horizon, the screening intervention dominated usual care. The probabilistic sensitivity analyses confirmed the robustness of these findings. The key drivers of the model were the proportion of melanomas detected by the screening procedure and the adherence of the target population to the screening programme. Conclusions: The screening programme proved to be a dominant option compared with usual care. These findings should prompt serious consideration of the design and implementation of a regional or national melanoma screening strategy within a National Health Service.